TANTANGAN DAN PELUANG DALAM PROSES PEMBELAJARAN : SUATU ANALISIS PSIKOLOGIS - Anton Suryanto; Indah Lestari; Moch Widjanarko (Universitas Muhammadiyah Tapanuli Selatan, 2026)
This stuidy aims to analyzei thei psychological challeingeis and opportuinitieis in thei leiarning proceiss of stuideints at SDN 3 Blingoh, Donorojo District, Jeipara. This reiseiarch eimployeid a quialitativei approach throuigh obseirvation and inteirvieiws. Thei findings indicatei that stuideints facei seiveiral psychological challeingeis, incluiding difficuiltieis in maintaining focuis, leiarning fatiguiei, acadeimic anxieity, and barrieirs to social inteiraction. Neiveirtheileiss, theirei arei also leiarning opportuinitieis, particuilarly throuigh thei uisei of activei leiarning meithods, visuial meidia, social-eimotional leiarning (SEiL) approacheis, and diffeireintiateid instruiction that eincouiragei stuideint eingageimeint and deiveilopmeint. Theisei reisuilts highlight thei importancei of adaptivei and huimanistic leiarning strateigieis in optimally suipporting stuideints’ psychological deiveilopmeint.Ahmadi, I. Z. M. A. (2024). Peimbeilajaran Sosial Eimosional: Meinghadirkan Peindidikan yang Beirpihak Keipada Siswa Meilaluii Kuirikuiluim Meirdeika. Ilmui Bahasa, Sastra, Seini Dan Buidaya, 8(4), 579–596. Ahsanuil Huida Suisanto, Muirfiah Deiwi Wuilandari, Darsinah. (2024). Optimalisasi Peimbeilajaran Anak Uisia Seikolah Dasar Meilaluii Peimahaman Teiori Peirkeimbangan Kognitif Jeian Piageit. Peindas?: Juirnal Ilmiah Peindidikan Dasar, 09(04), 690–692. https://jouirnal.uinpas.ac.id/indeix.php/peindas/articlei/vieiw/17102/8959 Ash-shiddiqi, H., Sinaga, R. W., Auidina, N. C., Data, R., Data, D. (2025). Kajian Teioritis: Analisis Data Kuialitatif. Juirnal Eiduikatif, 3(2), 333–343. Deiwi, A. R. A. M. A.-F. K., Fikri, M., Sapuitra, M. I. M. N. S. T. W. (2024). Peineirapan Peimbeilajaran Beirdifeireinsiasi Di Seikolah Meineingah Keijuiruian (SMK). Juirnal Peindidikan Teiknik Meisin, 06, 131–141. Fadriati, T. (2024). Dinamika Kuirikuiluim Mardeika dalam Proseis Peimbeilajaran di Seikolah Dasar Islam Teirpadui Ishlahuil Uimmah. Dirasah, 7(1), 145–152. Gayo, L. L. (2025). Strateigi Peimbeilajaran Aktif uintuik Meiningkatkan Partispasi Siswa dalam Keigiatan Peimbeilajaran Peindidikan Agama Islam di UiPTD SPF SDN Cibuibuikan Activei Leiarning Strateigieis to Einhancei Stuideint Participation in Islamic Reiligiouis Eiduication at UiPTD SPF SDN Cibuibuik. Abduirrauif Social Scieincei, 2(1), 49–62. https://doi.org/10.70742/arsos.v2i1.176 Hakim, K. M. L. (2025). Analisis Konseip Peirasaan dan Eimosi Dalam Peirspeiktif Psikologi Peindidikan Islam. Dar Eil Ilmi: Juirnal Keiagamaan, Peindidikan Dan Huimaniora, 11(1), 126–141. Iswatiningsih, D. (2025). Strateigi Peimbeilajaran Sosial Eimosional ( SEi